Pelayanan Pastoral Konseling terhadap Orang yang Belum Menikah dalam Konteks Kehidupan Modern - Pujiwati Pujiwati (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2020)
Pastoral counseling is one of the ministries within the church, namely to shepherd, guide, guide and mature the church's spirituality. In connection with marriage, pastoral counseling services are the spearhead in guiding and guiding couples who will enter into marriage. In the context of modern life, counseling services must be able to provide answers along with the challenges and struggles that develop in the congregation. People who are not married and will enter into marriage must receive guidance and guidance, so that they are not wrong in making decisions and choosing a life partner. Pastoral counseling is a scientific discipline whose success depends very much on the ability of God's servants to integrate the contributions of theology and psychology and the leading of the Holy Spirit. In pastoral counseling the counselor tries to guide the counselor into an ideal counseling conversational atmosphere. Thus, pastoral counseling for those who are not married is an important effort that needs to be done so that those who are not married can live as God wants.